Fa‘āliyyah Wasīlah Mudawwanah al-Fīdyū fī Ta‘līm Mahārah al-Kalām ladā Ṭullāb al-Madrasah al-Thānawiyyah al-Ḥukūmiyyah 1 al-Islāmiyyah bi Būkīttinggī - Yunitia Amelia NS; Rita Febrianta (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study focuses on problems in learning Speaking’s Ability, including monotonous teaching methods, students’ low speaking achievement, lack of interest and self-confidence, and the need for interactive media to support speaking practice. The population consisted of 353 students, with samples taken from two classes using purposive sampling: class E5 as the control class and class E9 as the experimental class, each consisting of 35 students. This study employed a quantitative approach with a quasi-experimental pre-test–post-test design. Data were analyzed using an independent sample t-test, and the research instruments were pre-test and post-test sheets. The results showed an effect size of 2.35, indicating a strong effect. The post-test scores of the experimental class were significantly higher than those of the control class, with a significance value of Sig. (2-tailed) = 0.000, which is lower than α = 0.05. This result led to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). These findings indicate that vlog media is effective in improving students’ speaking ability, confidence, and engagement in learning Maharah Kalam. Pedagogically, this study implies that teachers are encouraged to integrate vlog-based learning as an alternative instructional media to create more interactive and student-centered speaking activities. This research also contributes empirical evidence for the use of digital media in Arabic language instruction and recommends further studies to explore the application of vlog media in other language skills and educational contexts.